2018
DOI: 10.1007/s12103-018-9461-7
|View full text |Cite
|
Sign up to set email alerts
|

Is More Necessarily Better? School Security and Perceptions of Safety among Students and Parents in the United States

Abstract: The use of security measures within schools has increased dramatically over the past few decades. These proliferations are often touted by teachers, school administrators, politicians, and the public as necessary for improving student safety. Though research in this area is growing, we know little about how increased use of school security measures relates to both student and parental perceptions of school safety. Using data from wave one of the 2002 Educational Longitudinal Study, the current study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 54 publications
(86 reference statements)
1
25
0
Order By: Relevance
“…There were 18 studies that compared perceived school safety separately among sexes. Six studies found that boys were more likely to perceive their schools unsafe than girls [ 31 , 34 , 38 , 45 , 46 , 47 ], and five studies found that girls reported lower perceptions of school safety than boys [ 39 , 42 , 48 , 49 , 50 ]. Sexual minority youths were less likely to feel safe at school than non-sexual minority youths [ 22 , 33 , 34 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were 18 studies that compared perceived school safety separately among sexes. Six studies found that boys were more likely to perceive their schools unsafe than girls [ 31 , 34 , 38 , 45 , 46 , 47 ], and five studies found that girls reported lower perceptions of school safety than boys [ 39 , 42 , 48 , 49 , 50 ]. Sexual minority youths were less likely to feel safe at school than non-sexual minority youths [ 22 , 33 , 34 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…How do increasing concerns about school safety and security affect parents? For example, research has shown that the use of security measures (e.g., metal detectors) within schools to improve student safety make parents more wary of potential threats to children's safety at school (Mowen & Freng, ). How do differential disciplinary and surveillance practices at school by SES and race/ethnicity (Welch & Payne, ) affect parenting strains and well‐being differently?…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Analysis of the article content with the relevant categories "state", "health", and "education" shows that these publications are devoted to political (organizational and administrative), and police measures in the area of public security connected with health protection [13][14][15][16][17][18][19][20][21][22][23][24][25]; food security [26][27][28]; protection from threats and violence in educational sphere [29][30][31][32][33][34][35][36][37][38][39][40]; urban security [41][42][43][44][45][46][47]; and protection from crime and terrorism [48][49][50][51][52][53][54][55]. These life spheres and human behavior are evaluated for external risks and physical threats with preventive or reactive impacts on the environment and social relations being the factors and tools of protection from them.…”
Section: Discussionmentioning
confidence: 99%